Performance of Molecular Approaches for Aspergillus Detection and Azole Resistance Surveillance in Cystic Fibrosis - Guegan, Hélène; Chevrier, Sylviane; Belleguic, Chantal; Deneuville, Eric; Robert-Gangneux, Florence; Gangneux, Jean-Pierre (Frontiers in Microbiology, 2018)
Aspergillus fumigatus triazole resistance is an emerging concern for treating chronically infected/colonized patients. This study sought to evaluate the performance of PCR assays to detect Aspergillus fungi together with azole resistance in sputum samples from cystic fibrosis (CF) patients. In total, 119 sputum samples from 87 CF patients were prospectively processed for Aspergillus detection by means of mycological culture and four qPCR assays, 2 in-house methods and two commercial multiplex real-time PCR assays simultaneously detecting Aspergillus and the most relevant cyp51A gene mutations (MycoGENIE® and AsperGenius®). Azole susceptibility of A. fumigatus isolates was assessed using Etest® method and cyp51A gene mutation were characterized by sequencing. The overall rate of Aspergillus detection with the 4 qPCR assays ranged from 47.9% to 57.1%, contrasting with 42/119 (35.3%) positive cultures with A. fumigatus. The high sensitivity of PCR on sputum could then contribute to more effective grading of Aspergillus disease in CF patients. Five out of 41 isolated strains (12.2%) exhibited azole-resistant MIC patterns, three of which harbored cyp51A mutations and only 1/3 with the sequence TR34/L98H. Combined with culture, PCR assay achieved high sensitivity Aspergillus screening in CF samples. However, cyp51A targeting was only moderately effective for azole resistance monitoring, while Aspergillus resistance remains of great concern.